Migration flows within a fragmented global north: (re)placing the nexus between migration and development - Santos, Maria Teresa (2024)
The migration and development debate has traditionally been focused on the Global South, constructing a rigid division between a "developed Global North" and an "underdeveloped Global South". This article seeks to challenge this binary by situating the migration and development debate within the Global North. We argue that maintaining this North-South divide overlooks the effects of global capitalism in the North, where uneven development and intra-regional migration are also prevalent. By examining the processes of reterritorialization and neoliberal restructuring, this article highlights how migration flows within the European Union (EU), are expressions of unequal development across its member states. Through a quantitative analysis of economic indicators and the dynamics of migration flows, this article exposes the contradictions within global capitalism and makes the case for embedding the migration-development nexus within the Global North. The discussion emphasises the urgent need for critical research that investigates the impact of migration on development at both national and regional levels within the EU